Agrarian Reforms vis-à-vis Constitutionalism in India: A Comparative Analysis with Indonesia - Chhachhar, Varun; Niravita, Aprila; Verma, Karishma; Sankrit, Swikar (Journal of Indonesian Legal Studies, 2025)
This paper presents a comparative study on agrarian reforms in India and Indonesia, focusing on their constitutional foundations, legislative mechanisms, and judicial approaches. Agrarian reform has been central to the socio-economic transformation in both countries, where land ownership and rural livelihoods remain deeply significant. The main problem addressed is how these democracies have constitutionally managed land redistribution while balancing property rights and social justice. The study applies a doctrinal and comparative legal method, examining key constitutional provisions, legislative instruments, and judicial decisions. In India, reforms were initiated post-independence through the abolition of the zamindari system, later reinforced by constitutional amendments and the Ninth Schedule, evolving into broader property rights under Article 300A. Indonesia, by contrast, anchors its land reform agenda in the Basic Agrarian Law of 1960, which derives legitimacy from the 1945 Constitution and the state ideology of Pancasila, promoting social justice and state control over land. Findings suggest that India relies more on judicial interpretation to legitimize reform within its constitutional structure, while Indonesia adopts executive-led reforms grounded in centralized legal authority. The paper concludes that despite different institutional approaches, both nations illustrate how constitutional frameworks can be adapted to facilitate distributive justice through agrarian reform.